"A Smile I Could Not Explain": Educational Impact of an International Residency. (December 2015) - Evans, Shari D.; Yi, Charlie; Baker, Blossom B.; Crowley, Eugene; King, Debbie S.; Korinek, Adam W.; Reinsch, N. Lamar
This article reports a discourse analysis of journals from adult learners during a 1-week residency in Cape Town, South Africa. The theoretical posture is a critical dialogic perspective, making use of a postcolonial understanding of intercultural interactions. The purpose of the study was exploratory. The analysis suggests that demographic variables (e.g., race), prior international travel, and experiences during the residency influence the amount and pace of cognitive change. Results include both questions for future research and suggestions for educators.